The modern Kleinian approach to psychoanalytic technique clinical illustrations - Waska, Robert T. (Jason Aronson, 2010)
Robert Waska introduces a groundbreaking view of modern Kleinian psychoanalytic work applied to a wide spectrum of patients. The contemporary Kleinian approach of Analytic Contact redefines psychoanalytic psychotherapy as the treatment of choice for neurotic, borderline, and narcissistic patients with hope, change, and growth as a realistic goal.
Keywords: Klein, Melanie; Psychoanalysis